2001
DOI: 10.1111/j.1365-2621.2001.tb04618.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α‐Tocopherol, β‐Carotene, and Sodium Tripolyphosphate on Lipid Oxidation of Refrigerated, Cooked Ground Turkey and Ground Pork

Abstract: ␣ ␣ ␣ ␣ ␣-Tocopherol and ␤ ␤ ␤ ␤ ␤-carotene at 0.03% levels and sodium tripolyphosphate (STP) at 0.2% and 0.3% levels, alone and in combination, were added to ground turkey and ground pork. Hexanal was measured after cooking and storage at 4 Њ Њ Њ Њ ЊC for 2, 4, or 6 d. ␣ ␣ ␣ ␣ ␣-Tocopherol alone significantly reduced hexanal of stored, cooked, turkey but had no effect in pork. STP was more effective than ␣ ␣ ␣ ␣ ␣-tocopherol and a combination of ␣ ␣ ␣ ␣ ␣-tocopherol with STP resulted in enhanced antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Other factors include storage time and temperature, packaging material and cooking procedure (Van Elswyk, Dawson, & Sams, 1995). Here strategies were used to minimise warmed-over flavour (Wu & Sheldon, 1988) and organic products were not scored significantly (P = 0.22) higher for off-flavour despite reports elsewhere of lipid oxidation effects (Castellini, Mugnai, & Dal Basco, 2002a;Vara-Ubol & Bowers, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Other factors include storage time and temperature, packaging material and cooking procedure (Van Elswyk, Dawson, & Sams, 1995). Here strategies were used to minimise warmed-over flavour (Wu & Sheldon, 1988) and organic products were not scored significantly (P = 0.22) higher for off-flavour despite reports elsewhere of lipid oxidation effects (Castellini, Mugnai, & Dal Basco, 2002a;Vara-Ubol & Bowers, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous research showed that use of STP at low levels in combination with a-tocopherol resulted in an enhanced antioxidant effect (Vara-ubol and Bowers 2001). Hexanal content of cooked ground pork with 0.03% a-tocopherol plus 0.3% STP did not increase significantly during 6 d of storage (4 °C), and that of turkey increased only slightly.…”
Section: Introductionmentioning
confidence: 96%
“…Ascorbyl palmitate synergistically functions as an antioxidant with α‐tocopherol in oils/fats more than ascorbic acid due to its lipophilic nature. Many researchers have reported the significant antioxidant activity of α‐tocopherol and ascorbyl palmitate mixture in various foods (Bruun‐Jensen and others 1996a, 1996b; Gennadios and others 1997; Pirini and others 2000; Vara‐Ubol and Bowers 2001; Lin and Liang 2002).…”
Section: Introductionmentioning
confidence: 99%